Elastic-viscoplastic deformation models of salt rocks (Fracture and Structural Integrity, 2024)
Results of secondary creep tests for salt rock specimens were mathematically described. Elastic-viscoplastic modeling of viscous properties of salt rocks was based on elastoplastic models using a non-associated Mohr-Coulomb plastic flow and an associated volumetric yield criterion. In combination with these models the one-parameter Bingham and Duvaut-Lions as well as the two-parameter Perzyna and Perić viscoplasticity laws were analyzed. It’s been found that all laws being considered reflect an increase in longitudinal deformation of salt specimens during creep. It should be noted though that the yield criteria combined with the Perić law are characterized by relatively simple, stable parametric support and acceptable description of steady-state creep. The use of viscoplastic deformation model makes it possible to point out the fracture regions formed during creep according to a specified strength criterion.
Keywords: Salt rocks; Rib pillars; Elastic-viscoplastic model; Yield criteria; Mathematical modeling